Mulberry silk-containing homewear fabric and preparation method thereof
Through the blending technology of mulberry silk and carbon ball modified polylactic acid short fiber, home clothing fabrics with high breathability, anti-flushing and pilling properties and good elastic recovery capabilities were prepared, which solved the problem of insufficient wrinkle resistance, anti-flushing and pilling properties of blended fabrics, and met the comfort and durability needs of high-end home clothing.
Patent Information
- Application Number
- CN202510135613.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-07
AI Technical Summary
Mulberry silk and polylactic acid blended fabrics have shortcomings in wrinkle resistance, anti-flushing and pilling resistance and elastic recovery, making it difficult to meet the dual requirements of high-end home clothing for comfort and durability.
The blended yarn is prepared by using the blending ratio of 60/40, 70/30 or 80/20 of mulberry silk staple fiber and carbon ball modified polylactic acid staple fiber, and then through high needle and high density large circle woven and finishing treatment, a home garment fabric with high breathability and excellent anti-flushing and pilling properties is obtained.
It achieves high breathability, anti-fouling and pilling properties of the fabric and good elastic recovery ability, meeting the comfort and durability needs of high-end home clothing, and also has a good balance of flexibility and stiffness.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, and in particular to a home wear fabric containing mulberry silk and a preparation method thereof. Background Art
[0002] As people's requirements for comfort and functionality of home clothes continue to increase, the research and development of home clothes fabrics has gradually developed towards high breathability, softness, durability and environmental protection. As a natural fiber, mulberry silk has become the preferred material for high-end home clothes fabrics due to its unique luster, soft touch, excellent breathability and moisture absorption. However, mulberry silk also has some disadvantages, such as poor pilling resistance, insufficient mechanical properties, easy wrinkling and low durability, which limits its wide application in the field of daily home clothes. In addition, the high price of mulberry silk also increases the production cost of fabrics.
[0003] Polylactic acid (PLA) is a bio-based polymer material derived from renewable resources (such as corn starch). It has good mechanical properties, antibacterial properties and biodegradability, and is in line with the current trend of green environmental protection. The application of PLA fiber in the textile field is gradually increasing. Its advantages include high strength, good durability and certain wrinkle resistance. However, PLA fiber itself has poor softness, a hard feel, and poor air permeability and moisture absorption compared to natural fibers, which affects its comfort performance in home clothing fabrics. In addition, PLA fiber is prone to brittleness during long-term wear and washing, and its elastic recovery ability is limited.
[0004] Blending mulberry silk with polylactic acid to prepare home wear fabrics can combine the advantages of both, such as the softness and breathability of mulberry silk, and the mechanical properties and durability of polylactic acid. However, blending the two also has significant disadvantages. First, the physical and chemical properties of mulberry silk and polylactic acid are quite different, resulting in poor compatibility between the two, and problems such as fiber separation or insufficient interfacial bonding force are prone to occur after blending. Secondly, the stiffness of polylactic acid may weaken the softness of mulberry silk, and the wrinkle-prone nature of mulberry silk may also affect the wrinkle resistance of the blended fabric. In addition, blended fabrics still have deficiencies in anti-pilling and elastic recovery, making it difficult to meet the dual requirements of comfort and durability for high-end home wear. Summary of the invention
[0005] In view of this, the purpose of the present invention is to propose a home clothes fabric containing mulberry silk and a preparation method thereof, so as to solve the problems of poor wrinkle resistance, anti-pilling and elastic recovery ability of mulberry silk and polylactic acid blended fabrics, while taking into account the high air permeability, durability and environmental protection of the fabric, and meeting the requirements of high-end home clothes for comfort and functionality.
[0006] Based on the above purpose, the present invention provides a home clothing fabric containing mulberry silk, which is obtained by blending mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers to obtain blended yarns, which are then weaved and finished.
[0007] Furthermore, the blending ratio of the mulberry silk staple fibers and the carbon ball modified polylactic acid staple fibers is any one of 60 / 40, 70 / 30 and 80 / 20.
[0008] Furthermore, the preparation method of the carbon ball modified polylactic acid short fiber is as follows: S1: Disperse the solid nanocarbon spheres containing amino groups in N,N-dimethylformamide, perform ultrasonic treatment for 20-40 minutes, add palmitic acid, heat to 110-130°C, stir and react for 4-6 hours, centrifuge, wash, and vacuum dry to obtain alkyl chain-modified solid nanocarbon spheres; S2: Add polylactic acid to N,N-dimethylformamide, heat to 110-130°C, stir for 20-40min, then add alkyl chain modified solid nano carbon spheres, ultrasonicate for 20-40min, heat to 148-152°C, stir and reflux for 2.5-3.5h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; S3: The carbon ball modified polylactic acid is prepared into filaments through a melt spinning machine, and then cut into carbon ball modified polylactic acid short fibers.
[0009] Preferably, the average particle size of the solid nano-carbon spheres containing amino groups in step S1 is 400-600, and the amino group content is 4%-5%.
[0010] Preferably, in step S1, the weight ratio of the solid nano-carbon spheres containing amino groups, N,N-dimethylformamide and palmitic acid is 1.5-2.5:15-25:0.1-0.3.
[0011] Preferably, in step S2, the weight ratio of polylactic acid, N,N-dimethylformamide and alkyl chain modified solid nano-carbon spheres is 40-60:400-600:1.5-2.5.
[0012] Preferably, the intrinsic viscosity of the polylactic acid in step S2 is 1.1-1.3 dL / g.
[0013] Preferably, the fineness of the mulberry silk staple fiber is 1.2-1.6 dtex and the length is 35-40 mm.
[0014] Preferably, the carbon ball modified polylactic acid staple fibers have a fineness of 1.6-2.0 dtex and a length of 35-40 mm.
[0015] Furthermore, the present invention also provides a method for preparing a home wear fabric containing mulberry silk, comprising the following steps: (1) Skeining and cutting mulberry silk fibers into mulberry silk staple fibers; (2) mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers, opening, carding, drawing, roving, and spinning to obtain blended yarn; (3) Weaving the blended yarn through a large circular machine with high needle and high density to obtain a rough fabric; (4) Adding the raw fabric into the finishing liquid, treating it at 30-40°C for 40-50 minutes, and then setting it at 140-150°C for 3-8 minutes to obtain a home wear fabric containing mulberry silk.
[0016] Preferably, in the step (2), the twist coefficient of the blended yarn is 300-340 and the fineness is 12.4-16.8 tex.
[0017] Preferably, the warp density of the rough fabric in step (3) is 50-70 strands / cm, the weft density is 28-36 strands / cm, and the gram weight is 142-189 g / m 2 .
[0018] Preferably, in step (4), the bath ratio of the raw fabric to the finishing liquid is 1:15-25.
[0019] Preferably, the finishing liquid in step (4) is a softener aqueous solution with a concentration of 1.5wt%-2.5wt%, and the softener is polydimethylsiloxane.
[0020] Preferably, the heat setting temperature in step (4) is 140-150° C. and the time is 3-8 min.
[0021] Beneficial effects of the present invention: The present invention provides a home clothing fabric containing mulberry silk and a preparation method thereof. The fabric has high air permeability and excellent anti-pilling properties, is comfortable and durable to wear, has good elasticity, can quickly restore its shape after wearing, reduces the need for ironing, and exhibits a good balance between flexibility and a certain degree of stiffness, which can maintain the shape of the fabric and provide a comfortable wearing experience.
[0022] The present invention introduces modified solid nano-carbon balls into polylactic acid, which is then blended with mulberry silk into yarn, and the yarn is woven and finished to obtain home clothing fabric containing mulberry silk. The polylactic acid introduced with the modified solid nano-carbon balls significantly improves the anti-pilling property, wrinkle recovery and mechanical properties of the fabric. The present invention utilizes the cross-linking effect of amino groups on the surface of the solid nano-carbon balls and polylactic acid to improve the elasticity and anti-wrinkle property of the fabric, and utilizes the ball effect of the nano-carbon balls to improve the anti-pilling property of the fabric. At the same time, the grafting of alkyl chains effectively adjusts the balance between flexibility and stiffness, and improves the air permeability and structural stability. DETAILED DESCRIPTION
[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0024] The softener in the specific embodiment of the present invention is polydimethylsiloxane, purchased from Shandong Luxin Chemical Industry with the item number of lx-201; the solid nano-carbon spheres containing amino groups on the surface were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with an average particle size of 520 nm and an amino content of 4.87%; the solid nano-carbon spheres containing carboxyl groups on the surface were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with an average particle size of 510 nm and a carboxyl content of 4.67%; polylactic acid was purchased from NatureWorks with an intrinsic viscosity of 1.204 dL / g.
[0025] Embodiment 1: (1) 1.2 dtex silk fibers are cut into short fibers with a length of 35 mm; (2) 1.5 g of solid carbon nanospheres with amino groups on the surface were dispersed in 15 g of N,N-dimethylformamide, ultrasonicated for 20 min, and then 0.1 g of palmitic acid was added. The temperature was raised to 110 °C, stirred for 4 h, centrifuged, washed, and vacuum dried to obtain alkyl chain-modified solid carbon nanospheres. (3) Add 40 g of polylactic acid to 400 g of N,N-dimethylformamide, heat to 110 °C, stir for 20 min, then add 1.5 g of alkyl chain modified solid nano carbon spheres, ultrasonicate for 20 min, heat to 148 °C, stir and reflux for 2.5 h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; (4) preparing the carbon ball modified polylactic acid into filaments with a fineness of 1.6 dtex through a melt spinning machine, and then shearing them into carbon ball modified polylactic acid short fibers with a length of 35 mm; (5) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 80 / 20, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 300 and a fineness of 12.4 tex; (6) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 50 strands / cm, a weft density of 28 strands / cm, and a gram weight of 142 g / m 2 of coarse fabrics; (7) The crude fabric was added into water at a bath ratio of 1:15, and a softener was added at a softener concentration of 1.5 wt %. The fabric was treated at 30 ° C for 40 min, and then fixed at 140 ° C for 3 min to obtain a home wear fabric containing mulberry silk.
[0026] Embodiment 2: (1) 1.4 dtex silk fibers are cut into short fibers with a length of 38 mm; (2) 2 g of solid carbon nanospheres containing amino groups on the surface were dispersed in 20 g of N,N-dimethylformamide, ultrasonicated for 30 min, and then 0.2 g of palmitic acid was added. The temperature was raised to 120 °C, stirred for 5 h, centrifuged, washed, and vacuum dried to obtain alkyl chain-modified solid carbon nanospheres. (3) Add 50 g of polylactic acid to 500 g of N,N-dimethylformamide, heat to 120 °C, stir for 30 min, then add 2 g of alkyl chain modified solid nano carbon spheres, ultrasonicate for 30 min, heat to 150 °C, stir and reflux for 3 h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; (4) preparing the carbon ball modified polylactic acid into filaments with a fineness of 1.8 dtex through a melt spinning machine, and then shearing them into carbon ball modified polylactic acid short fibers with a length of 38 mm; (5) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 70 / 30, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 320 and a fineness of 14.5 tex; (6) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 60 strands / cm, a weft density of 32 strands / cm, and a gram weight of 165 g / m 2 of coarse fabrics; (7) The crude fabric was added into water at a bath ratio of 1:20, and a softener was added at a softener concentration of 2 wt %. The fabric was treated at 35 ° C for 45 min, and then fixed at 145 ° C for 5 min to obtain a home wear fabric containing mulberry silk.
[0027] Embodiment 3: (1) 1.6 dtex silk fibers are cut into short fibers with a length of 40 mm; (2) 2.5 g of solid carbon nanospheres containing amino groups on the surface were dispersed in 25 g of N,N-dimethylformamide, ultrasonicated for 40 min, and then 0.3 g of palmitic acid was added. The temperature was raised to 130 °C, stirred for 6 h, centrifuged, washed, and vacuum dried to obtain alkyl chain-modified solid carbon nanospheres. (3) Add 60 g of polylactic acid to 600 g of N,N-dimethylformamide, heat to 130 °C, stir for 40 min, then add 2.5 g of alkyl chain modified solid nano carbon spheres, ultrasonicate for 40 min, heat to 152 °C, stir and reflux for 3.5 h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; (4) preparing the carbon ball modified polylactic acid into filaments with a fineness of 2.0 dtex through a melt spinning machine, and then shearing them into carbon ball modified polylactic acid short fibers with a length of 40 mm; (5) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 60 / 40, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 340 and a fineness of 16.8 tex; (6) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 70 strands / cm, a weft density of 36 strands / cm, and a gram weight of 189 g / m 2 of coarse fabrics; (7) The crude fabric was added into water at a bath ratio of 1:25, and a softener was added at a softener concentration of 2.5 wt %. The fabric was treated at 40 ° C for 50 min, and then fixed at 150 ° C for 8 min to obtain a home wear fabric containing mulberry silk.
[0028] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the solid nano-carbon spheres containing amino groups on the surface in step (2) are replaced by solid nano-carbon spheres containing carboxyl groups on the surface; The specific steps are as follows: (1) 1.4 dtex silk fibers are cut into short fibers with a length of 38 mm; (2) Disperse 2 g of solid carbon nanospheres with carboxyl groups on the surface in 20 g of N,N-dimethylformamide, ultrasonicate for 30 min, add 0.2 g of palmitic acid, heat to 120 °C, stir for 5 h, centrifuge, wash, and vacuum dry to obtain modified solid carbon nanospheres; (3) Add 50 g of polylactic acid to 500 g of N,N-dimethylformamide, heat to 120 °C, stir for 30 min, then add 2 g of modified solid nano carbon spheres, ultrasonicate for 30 min, heat to 150 °C, stir and reflux for 3 h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; (4) preparing the carbon ball modified polylactic acid into filaments with a fineness of 1.8 dtex through a melt spinning machine, and then shearing them into carbon ball modified polylactic acid short fibers with a length of 38 mm; (5) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 70 / 30, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 320 and a fineness of 14.4 tex; (6) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 60 strands / cm, a weft density of 32 strands / cm, and a gram weight of 164 g / m 2 of coarse fabrics; (7) The crude fabric was added into water at a bath ratio of 1:20, and a softener was added at a softener concentration of 2 wt %. The fabric was treated at 35 ° C for 45 min, and then fixed at 145 ° C for 5 min to obtain a home wear fabric containing mulberry silk.
[0029] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the alkyl chain-modified solid nano-carbon spheres in step (3) are replaced by solid nano-carbon spheres containing amino groups on the surface; The specific steps are as follows: (1) 1.4 dtex silk fibers are cut into short fibers with a length of 38 mm; (2) Add 50 g of polylactic acid to 500 g of N,N-dimethylformamide, heat to 120 °C, stir for 30 min, then add 2 g of solid nano carbon spheres containing amino groups on the surface, ultrasonicate for 30 min, heat to 150 °C, stir and reflux for 3 h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere-modified polylactic acid; (3) preparing the carbon ball modified polylactic acid into filaments with a fineness of 1.8 dtex through a melt spinning machine, and then shearing them into carbon ball modified polylactic acid short fibers with a length of 38 mm; (4) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 70 / 30, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 320 and a fineness of 14.3 tex; (5) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 60 strands / cm, a weft density of 32 strands / cm, and a gram weight of 164 g / m 2 of coarse fabrics; (6) The crude fabric was added into water at a bath ratio of 1:20, and a softener was added at a softener concentration of 2 wt %. The fabric was treated at 35 ° C for 45 min, and then fixed at 145 ° C for 5 min to obtain a home wear fabric containing mulberry silk.
[0030] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the amount of palmitic acid in step (2) is adjusted to 1 g; The specific steps are as follows: (1) 1.4 dtex silk fibers are cut into short fibers with a length of 38 mm; (2) 2 g of solid carbon nanospheres containing amino groups on the surface were dispersed in 20 g of N,N-dimethylformamide, ultrasonicated for 30 min, and then 1 g of palmitic acid was added. The temperature was raised to 120 °C, stirred for 5 h, centrifuged, washed, and vacuum dried to obtain alkyl chain-modified solid carbon nanospheres. (3) Add 50 g of polylactic acid to 500 g of N,N-dimethylformamide, heat to 120 °C, stir for 30 min, then add 2 g of alkyl chain modified solid nano carbon spheres, ultrasonicate for 30 min, heat to 150 °C, stir and reflux for 3 h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; (4) preparing the carbon ball modified polylactic acid into filaments with a fineness of 1.8 dtex through a melt spinning machine, and then shearing them into carbon ball modified polylactic acid short fibers with a length of 38 mm; (5) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 70 / 30, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 320 and a fineness of 14.5 tex; (6) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 60 strands / cm, a weft density of 32 strands / cm, and a gram weight of 165 g / m 2 of coarse fabrics; (7) The crude fabric was added into water at a bath ratio of 1:20, and a softener was added at a softener concentration of 2 wt %. The fabric was treated at 35 ° C for 45 min, and then fixed at 145 ° C for 5 min to obtain a home wear fabric containing mulberry silk.
[0031] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that polylactic acid and alkyl chain-modified solid nano-carbon spheres are directly mixed and then melt-spun; The specific steps are as follows: (1) 1.4 dtex silk fibers are cut into short fibers with a length of 38 mm; (2) Alkyl chain modified solid nano carbon spheres and carbon sphere modified polylactic acid were mixed in a weight ratio of 2:50, and then prepared into filaments with a fineness of 1.8 dtex by a melt spinning machine, and then cut into carbon sphere modified polylactic acid short fibers with a length of 38 mm; (3) Mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers at a blending ratio of 70 / 30, opening, carding, drawing, roving, and spun yarn to obtain a blended yarn with a twist coefficient of 320 and a fineness of 14.6 tex; (4) The blended yarn is woven through a high-needle, high-density circular knitting machine to obtain a warp density of 60 strands / cm, a weft density of 32 strands / cm, and a gram weight of 167 g / m 2 of coarse fabrics; (5) The crude fabric was added into water at a bath ratio of 1:20, and a softener was added at a softener concentration of 2 wt %. The fabric was treated at 35 ° C for 45 min, and then fixed at 145 ° C for 5 min to obtain a home wear fabric containing mulberry silk.
[0032] Performance Test: Air permeability: Different positions of the fabrics prepared in the examples and comparative examples were selected and tested using an air permeability meter according to GB / T 5453-1997 to obtain the air permeabilities of the samples at different positions and take the average value. The results are shown in Table 1.
[0033] Anti-pilling property: The fabrics prepared in the examples and comparative examples were cut into squares with a side length of 15 cm and tested using a fabric flat grinding instrument. According to GB / T4802.2-2008, wool abrasives were used and subjective ratings were made after flat grinding 2000 times. The results are shown in Table 1.
[0034] Wrinkle recovery: The wrinkle recovery angle of the fabrics prepared in the examples and comparative examples was tested according to the horizontal method in GB / T 3819-1997 "Determination of Crease Recovery of Textile Fabrics - Recovery Angle Method" standard. The test was conducted 5 times in each weft direction and the average value was calculated. The results are shown in Table 1.
[0035] Rigidity and flexibility: According to GB / T 18318.1-2009, the bending length of the fabrics prepared in the examples and comparative examples was measured, and the bending resistance length of the fabrics was calculated to evaluate the rigidity and flexibility of the samples. The results are shown in Table 1.
[0036]
[0037] Data Analysis: It can be seen from the data of Examples 1-3 in Table 1 that the home clothing fabric containing mulberry silk prepared by the present invention has high air permeability and anti-pilling properties, and has a high wrinkle recovery, indicating that it has good elasticity. At the same time, the anti-bending length is moderate, indicating that it has a certain stiffness while having good flexibility, and can provide a good wearing experience while maintaining the shape of the fabric.
[0038] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the amino groups on the surface of the solid nano-carbon spheres can effectively improve the anti-pilling properties of the fabric, and further improve the wrinkle recovery and bending length. This is mainly because the amino groups on the surface of the solid nano-carbon spheres provide grafting sites for the alkyl chains on the one hand, and form cross-links with polylactic acid on the other hand. The solid nano-carbon spheres cross-linked in the polylactic acid can play a ball effect, and the alkyl chains are interspersed in the molecular chains of the polylactic acid, thereby enhancing the flexibility and slippage of the molecular chains, improving the elasticity and wrinkle resistance of the fabric, and at the same time improving the mechanical properties and durability of the fabric.
[0039] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that the grafting of alkyl chains can improve the air permeability and wrinkle recovery of the fabric, and adjust the balance between flexibility and stiffness. This is mainly because the grafting of alkyl chains, on the one hand, prevents excessive cross-linking of solid nano-carbon spheres in polylactic acid, and on the other hand, is interspersed in the molecular chain to enhance the flexibility of the molecular chain, thereby effectively adjusting the flexibility and stiffness.
[0040] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that excessive grafting of palmitic acid will lead to a decrease in the anti-pilling and anti-bending length of the fabric. This is mainly because excessive grafting of palmitic acid will make it difficult for solid nano-carbon balls to be grafted into polylactic acid, thereby causing a decrease in the dispersion of solid nano-carbon balls in polylactic acid, thereby weakening the rolling effect and cross-linking effect of the solid nano-carbon balls, resulting in a weakening of the interaction force between polylactic acid molecular chains, a decrease in the mechanical properties and structural stability of the fabric, and ultimately affecting the anti-pilling and anti-bending properties.
[0041] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that melt spinning directly after mixing polylactic acid and alkyl chain modified solid nano-carbon spheres will lead to a decrease in anti-pilling and bending length. This is mainly because the compatibility between polylactic acid and the alkyl chain is poor, and the alkyl chain is difficult to fully stretch, which hinders the cross-linking of polylactic acid and the amino groups on the surface of the solid nano-carbon spheres, thereby resulting in the reinforcing effect of the solid nano-carbon spheres in the polylactic acid.
[0042] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A home wear fabric containing mulberry silk, characterized in that: The blended yarn is obtained by blending mulberry silk staple fiber and carbon ball modified polylactic acid staple fiber, and then weaving and finishing; The blending ratio of the mulberry silk staple fiber and the carbon ball modified polylactic acid staple fiber is any one of 60 / 40, 70 / 30 and 80 / 20; The preparation method of the carbon ball modified polylactic acid staple fiber is as follows: S1: Disperse the solid nanocarbon spheres containing amino groups in N,N-dimethylformamide, perform ultrasonic treatment for 20-40 minutes, add palmitic acid, heat to 110-130°C, stir and react for 4-6 hours, centrifuge, wash, and vacuum dry to obtain alkyl chain-modified solid nanocarbon spheres; S2: Add polylactic acid to N,N-dimethylformamide, heat to 110-130°C, stir for 20-40min, then add alkyl chain modified solid nano carbon spheres, ultrasonicate for 20-40min, heat to 148-152°C, stir and reflux for 2.5-3.5h, rotary evaporate, wash, and vacuum dry to obtain carbon sphere modified polylactic acid; S3: preparing the carbon ball modified polylactic acid into filaments through a melt spinning machine, and then cutting them into carbon ball modified polylactic acid short fibers; The average particle size of the solid nano-carbon spheres containing amino groups in step S1 is 400-600, and the amino group content is 4%-5%; In the step S1, the weight ratio of the solid nano-carbon spheres containing amino groups, N,N-dimethylformamide and palmitic acid is 1.5-2.5:15-25:0.1-0.3; In the step S2, the weight ratio of polylactic acid, N,N-dimethylformamide and alkyl chain modified solid nano carbon spheres is 40-60:400-600:1.5-2.
5.
2. The home wear fabric containing mulberry silk according to claim 1, characterized in that: The intrinsic viscosity of the polylactic acid in step S2 is 1.1-1.3 dL / g.
3. The home wear fabric containing mulberry silk according to claim 1, characterized in that: The fineness of the mulberry silk staple fibers is 1.2-1.6 dtex, and the length is 35-40 mm.
4. The home wear fabric containing mulberry silk according to claim 1, characterized in that: The carbon ball modified polylactic acid short fibers have a fineness of 1.6-2.0 dtex and a length of 35-40 mm.
5. A method for preparing a home wear fabric containing mulberry silk according to claim 1, characterized in that: The following steps are involved: (1) Skeining and cutting mulberry silk fibers into mulberry silk staple fibers; (2) mixing mulberry silk staple fibers and carbon ball modified polylactic acid staple fibers, opening, carding, drawing, roving, and spinning to obtain blended yarn; (3) Weaving the blended yarn through a large circular machine with high needle and high density to obtain a rough fabric; (4) Adding the raw fabric into the finishing liquid, treating it at 30-40°C for 40-50 minutes, and then setting it at 140-150°C for 3-8 minutes to obtain a home wear fabric containing mulberry silk.
6. The method for preparing home clothes fabric containing mulberry silk according to claim 5, characterized in that: In the step (2), the twist coefficient of the blended yarn is 300-340 and the fineness is 12.4-16.8 tex.
7. The method for preparing home wear fabric containing mulberry silk according to claim 5, characterized in that: The warp density of the rough fabric in step (3) is 50-70 strands / cm, the weft density is 28-36 strands / cm, and the gram weight is 142-189 g / m 2 .
8. The method for preparing home wear fabric containing mulberry silk according to claim 5, characterized in that: In the step (4), the bath ratio of the raw fabric to the finishing liquid is 1:15-25.
9. The method for preparing home wear fabric containing mulberry silk according to claim 5, characterized in that: In the step (4), the finishing liquid is a softener aqueous solution with a concentration of 1.5wt%-2.5wt%, and the softener is polydimethylsiloxane.
10. The method for preparing home wear fabric containing mulberry silk according to claim 5, characterized in that: The temperature of the heat setting in step (4) is 140-150° C. and the time is 3-8 minutes.
Citation Information
Patent Citations
Fibre structure of carbon nano tube / nano oxide nano composite material and preparation method and use thereof
CN101139742A
Infant garment made from polylactic acid
CN104432665A
Preparation method of high-elastic softening knitted fabric
CN105332153A
Breathable mulching film plastic and preparation method thereof
CN116804299A
Monofilaments of lactic acid based resin excellent in processability for secondary processing and weatherability
JP2000192333A